Efficient utilization of Shuanghuanglian medicine residues by microbial transformation with flavonoid glycosides-hydrolyzing strains - Ma, Xingwang; Chen, Ying; Li, Lili; Wang, Tianwei; Teng, Kunling; Su, Junchang; Li, Lei; Li, Liangliang; Li, Heping; Diao, Wentao; Chen, Guocan; Wang, Jiwen; et al. (Frontiers in Microbiology, 2025)
Shuanghuanglian, a traditional Chinese medicine, is well-known for its bioactive compounds, such as flavonoids, which offer significant health benefits. However, the production of Shuanghuanlian generates substantial pharmaceutical residues, which are often discarded as waste, posing significant environmental and economic challenges. To date, research on repurposing these medicine residues has been limited. This study utilized beneficial microbes to efficiently extract and utilize the residual bioactive compounds. Notably, a newly isolated Lactiplantibacillus plantarum strain LLB exhibited remarkable efficiency in converting flavonoid glycosides (e.g., phillyrin and luteoloside) into their corresponding aglycones. When combined synergistically with Bacillus subtilis and Saccharomyces cerevisiae, strain LLB maintained robust flavonoid glycoside conversion while enhancing lactobacilli viability in the fermented medicine residues. As a feed additive for broiler chickens, the fermented residue not only boosted antioxidant (superoxide dismutase) and anti-inflammatory (IL-10) markers, but also preserved growth performance and meat quality. Furthermore, the fermented residue modulated the gut microbiome, increasing Rikenella while reducing Elusimicrobiota and Parabacteroides abundances. Our findings demonstrate that microbial transformation of Shuanghuanglian residues offers a sustainable strategy for waste valorization and a novel feed additive for enhancing animal health.